THE IMPACTS OF ELECTIONS ON ECONOMICS IN INDONESIA - Muchlis, Zaini (IJISH (International Journal of Islamic Studies and Humanities), 2018)
Money politic or vote buying in the election is something has plagued all the societies that claimed the application of democratic form in governance. The minority is able to monopolize the votes of the majority in their favor using financial sufficiency, political promises and the issues of mass media. This phenomenon can lead to bribery, perjury and treason that have negative impact on the economy of Indonesia. The researcher used analytical method to explain various aspects of the phenomenon of buying electoral votes and its impact on the economic life in Indonesia. The researcher finally found two significant results. First, vote buying is a major cause of political and administrative corruption in Indonesia. It is the main incubator breeding corrupt leaders, which have negative impact towards economic life in Indonesia such as the increase number of poverty, unstable economy, enrich among political elites, and arbitrariness in determining economic policies taken by the authorities pursuing their own interests. Second, vote buying is widely spread and easily found in the life of the Indonesian society, it seems like an established habit that is hard to eradicate.